Literature Review: Legalisasi Dokumen Elektronik Menggunakan Tanda Tangan Digital sebagai Alternatif Pengesahan Dokumen di Masa Pandemi - Trihastuti Yuniati; Muhammad Fajar Sidiq (Ikatan Ahli Informatika Indonesia (IAII), 2020)
With a pandemic that has hit almost all over the world, the government has issued policies for doing physical distancing and work from home (WFH). That policies made a very significant change in the way people work and interact. WFH applies in most fields of work, one of them is in education. WFH and online learning require every student, lecturer and employee to work online from home. In fact, there are many activities that require validation in the form of a signature, both for academic and non-academic matters. Digital signature is a technology that can be applied to overcome this problem. There are various algorithms and schemes that users can implement. This paper will present the results of a review of several literature related to the implementation of digital signatures. The results of this literature review are expected to provide the readers with an insight of the implementation of digital signatures in various fields, as well as their strengths and weaknesses.